Uji Kinerja Metode Asam Askorbat pada Pengukuran Kadar Fosfat dalam Air Permukaan secara Spektrofotometri : Performance Test of the Ascorbic Acid Method on the Measurement of Phosphate Levels in Surface Water by Spectrophotometry - Ardina Purnama Tirta; Anom Cahyotomo; Herawati; Inda Mapiliandari; Esti Isnainiyati (JURNAL SAINS TEKNOLOGI & LINGKUNGAN, 2023)
Phosphorus is easily found in its compound form in nature, namely as phosphate (PO43-). Phosphates have an essential role in limiting nutrients for plants and animals. An increase of phosphate in the aquatic environment can cause unwanted impacts, including blooming algae, low dissolved oxygen, and the death of certain aquatic animals. Determination of phosphate in the aquatic environment is critical to do as a monitoring effort. The performance test of the phosphate determination method needs to be carried out to provide quality assurance of the test results. In this study, the performance test of the ascorbic acid method was carried out in the determination of phosphate levels by spectrophotometry. The modification was made by changing the sample volume from 50 mL to 10 mL. The performance test on the linearity parameter obtained the regression equation y = 0.6379x + 0.0083 with a correlation coefficient value, r = 0.9999 in the concentration range of 0.05 – 1.00 mg/L P_PO4. The instrument detection limit (IDL), method detection limit (MDL), and the theoretical limit of quantitation (LoQ) obtained were 0.01 mg/L, 0.02 mg/L, and 0.04 mg/L P_PO4, respectively. As a precision test, the value of the relative standard deviation percentage (%RSD) is 1.07%. The range of percent recovery (%recovery) obtained was 99 – 102%. The relative uncertainty value was obtained at 2.5% at 0.40 mg/L P_PO4 concentration. Robustness tests at 50 mL and 10 mL sample volumes gave acceptable F-test and t-test results. The results showed that the ascorbic acid method in determining phosphate levels by spectrophotometry with modification of the sample volume gave acceptable method performance results.